Coping with Invisible Threats: Nuclear Radiation and Science Dissemination in Maoist China. Issue 3 (1st September 2018) - Matten, Marc andre
Abstract: During the early People's Republic of China (PRC) era the science dissemination campaign ( kexue puji ) aimed at conveying not only scientific knowledge related to daily life concerns but also knowledge about invisible dangers, most prominently those emanating from weapons of mass destruction such as nuclear weapons. The immediate task of the young PRC after the outbreak of the Korean War in 1950 was to make nuclear radiation visible by iconic metaphors and to teach the population about the dangers of an invisible nuclear fallout should the United States decide to use nuclear weapons. By focusing on the most characteristic media in science dissemination of the 1950s such as the Newsletter of Science Dissemination ( Kexue puji tongxun ), as well as popular science journals such Science Pictorial ( Kexue huabao ) and Knowledge Is Power ( Zhishi jiushi liliang ), this article shows how the state used metaphors of the invisible to influence social and political behavior. Convincing the barely literate peasant and the inchoately educated worker of possible dangers in the Cold War required a different epistemology of knowledge than in traditional society. This resulted in a further refinement of Maoist science philosophy that integrated materialism into science policies.